"Why Do You Stand Looking Up Toward Heaven?" New Testament Eschatology at the Turn of the Millennium - Hays, Richard B. (Modern theology, 2000)
Apocalyptic narrative and apocalyptic expectation are integral to the logic of the gospel. This essay surveys and critiques three unsatisfactory strategies for reinterpreting the gospel in non-apocalyptic terms: the Johannine "vertical" eschatology of union with Christ, the Jesus Seminar's construction on a non-apocalyptic Jesus, and N. T. Wright's reading of synoptic apocalyptic passages as a symbolic references to events that occurred already in the first century. Christian theology cannot dispense with a future-oriented apocalyptic eschatology. Seven reasons for this claim are set forth and explained. The concluding part of the essay suggests that the difficulty of accepting apocalyptic eschatology has often been overstated and observes that "intratextual" Christian theology will necessarily interpret the story of Jesus in apocalyptic categories.